Exploring the experiences of cancer patients: What drives them to seek treatment outside their residential area and what are the experiences resulting from that decision? A qualitative study - Jeehee Pyo; Mina Lee; Haneul Lee; Minsu Ock (PLoS ONE, 2025)
Background The centralizing cancer care has been a persistent trend, often justified by the volume-outcome relationship. However, this trend raises concerns about potential negative impacts, such as increased patient travel burden, treatment delays, and worsened regional disparities in cancer care. Consequently, there is a growing need for the establishment of a regional comprehensive cancer care system to minimize these disparities. In this study, we explored the treatment experiences of cancer patients who received care at medical institutions outside their residential areas to understand their overall experiences with cancer care and identify areas for improvement in the healthcare system. Methods The participants in this study were 7 residents of Ulsan Metropolitan City who had experienced hospitalization for cancer treatment at a medical institution in another region. In-depth interviews were conducted with each participant for about an hour, exploring the participants’ experiences in the process of cancer diagnosis, treatment, and follow-up management. A semi-structured guide was used for in-depth interviews. Results The participants experienced fear after receiving an unexpected possibility of cancer diagnosis as a biopsy result. They wanted a definitive diagnosis as soon as possible, which was not realistic, as a tertiary general hospital in Ulsan featured waiting times of at least 6 months. Participants were overwhelmed with anxiety, and continued searching for information on the disease by themselves. Most of the processes of cancer diagnosis, treatment, and follow-up management at medical institutions in other regions were a series of hardships. Participants had partially recovered, but were still concerned about becoming unwell. Participants stated that reliable medical institutions in the region and sufficient information related to cancer are needed to improve the quality of life of cancer patients. Conclusion The results of this study reveal that cancer patients face various challenges throughout their long journey of treatment. To establish a comprehensive regional cancer care system, it is necessary to expand the availability of quality cancer care across all regions, strengthen the coordination function of primary care institutions, and develop post-discharge cancer management systems using patient-reported outcomes.